Social change agent training program tailored to occupational therapists’ needs: a design-based study protocol - Rahimaly, Sarah; Beaudoin, Michaël; Bédard, Denis; Hudon, Anne; Jasmin, Emmanuelle; Verville, France; Carrier, Annie (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background As social change agents (SCAs), occupational therapists (OTs) are expected to defend the rights of their clients, advocate for and with them, and try to influence organizational and political decision-makers. However, OTs do not generally feel equipped to take effective action. The overall goal of this research partnership is to support practising OTs in acquiring the knowledge and skills required to act as SCAs through a specific SCA training program and a toolkit that summarizes the key training points. Methods The study will include three iterative phases (conceptualization, implementation and evaluation) and use a participatory process. The design of the training program and toolkit will draw on the expertise of the researchers (theoretical knowledge), a professional provincial partner and study participants (experiential knowledge). To evaluate the training program and toolkit, a self-administered evaluation questionnaire, facilitator observation grid and semi-structured guide designed to facilitate focus group discussions will be used. The quantitative and qualitative data will be analyzed using descriptive statistics and thematic analysis, respectively. The results of the initial implementation and evaluation phases will inform improvement of the training program and toolkit before starting the cycle with the following groups. Discussion In addition to training about 100 OTs, this study will produce three main benefits: 1) development of two products, namely the SCA training program and toolkit, that are easy to reuse and potentially transferable to other professionals; 2) ownership of these products by the partner through its close involvement in all stages of the study; and 3) development of a sustainable partnership between a team of researchers and a recognized organization with networks across Canada and internationally. These three spin-offs will provide a solid basis for an increasing number of permanent implementation initiatives, in Québec and elsewhere in Canada, not just in occupational therapy but also in other professions.